Role and Place of Hyperbaric Oxygenation in Hepatic Failure - P. N. Savilov (Общая реаниматология, 2009)
Objective: to define the role and place of hyperbaric oxygenation (HBO) in the treatment and prevention of liver cell failure. Material and methods. The results of the author’s own studies and the data available in the literature on the impact of HBO on the functional state of the liver and the whole organism in liver cell failure were analyzed. Results: The therapeutic and preventive effects of HBO during therapy for liver cell failure were due to the ability of hyperbaric oxygen to regulate metabolic processes in the sick organism. By eliminating the impaired hepatic neutralization of ammonia, hyperbaric oxygen corrects its extrahepatic reactions in rendering harmless various toxic substances, which become active in response to the ammonia-neutralizing dysfunction of hepatocytes. This prevents the development of endogenous ammonia intoxication. In liver cell failure, HBO concurrently stimulates hepatic protein synthesis function and the cell link of the body’s antimicrobial protection. The therapeutic effect of HBO is not always attended by the elimination of hepatic hypoxia and the sick organism’s hypoxemia, but it persists long in the posthyperoxic period. Conclusion: HBO can and must be an integral part of complex therapy for liver cell failure. Key words: hyperoxia, treatment, liver, failure.